2022
DOI: 10.5334/ijic.5677
|View full text |Cite
|
Sign up to set email alerts
|

What Can Canada Learn From Accountable Care Organizations: A Comparative Policy Analysis

Abstract: Introduction: Accountable Care Organizations (ACOs), implemented in the United States (US), aim to reduce costs and integrate care by aligning incentives among providers and payers. Canadian governments are interested adopting such models to integrate care, though comparative studies assessing the applicability and transferability of ACOs in Canada are lacking. In this comparative study, we performed a narrative literature review to examine how Canadian health systems could support ACO models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
(107 reference statements)
0
5
0
3
Order By: Relevance
“…Für die Bewertung von ACOs ausgeschlossen wurden Artikel, welche sich nicht auf Medicare ACOs beziehen, d. h. Artikel zu ACOs mit kommerziellen Krankenversicherungen oder Medicaid-ACOs. Diese Ausschlusskriterien erhöhen die Validität des Reviews und unterscheiden es von vorangegangen Übersichtsarbeiten 6 28 29 . Mit Hilfe des Snowballing-Verfahrens wurden weitere Artikel identifiziert.…”
Section: Methodikunclassified
See 1 more Smart Citation
“…Für die Bewertung von ACOs ausgeschlossen wurden Artikel, welche sich nicht auf Medicare ACOs beziehen, d. h. Artikel zu ACOs mit kommerziellen Krankenversicherungen oder Medicaid-ACOs. Diese Ausschlusskriterien erhöhen die Validität des Reviews und unterscheiden es von vorangegangen Übersichtsarbeiten 6 28 29 . Mit Hilfe des Snowballing-Verfahrens wurden weitere Artikel identifiziert.…”
Section: Methodikunclassified
“…Durch diesen mittelbaren Zugriff des Ministeriums fungiert Medicare als eine Plattform, um politisch gewollte Veränderungen in der Versorgung in den USA voranzutreiben[24].Aus 2358 Ergebnissen in der initialen Suche wurden nach Durchsicht der Abstracts für die Analyse 60 Artikel herangezogen, wovon 31 Aussagen zu Versorgungskosten, 18 Aussagen zu Versorgungsqualität sowie 8 Aussage zu beiden Aspekten beinhalten, dies inkludiert 6 Reports im Auftrag von oder direkt durchgeführt von US-Regierungsstellen. Berücksichtigt wurden auch Ergebnisse von 3 vorherigen Reviews[6,28,29]. Alle Studien hatten retrospektiven Charakter, da prospektive randomisierte Studien im Setting der Intervention nicht möglich sind.…”
unclassified
“…We also measured a set of factors for use as covariates in analysis. These included the number of performance management activities (a count across the following: individual financial rewards, nonfinancial awards/recognition, physician performance on quality reports, and one-on-one review of physician quality performance) and the types of ownership (categorical, including, by an independent owner, a larger physician group, a hospital, a health care system, or other), as past research has indicated that the explicitness of performance management activities and types of ownership were key determinants of ACO performance (Peckham et al, 2019). We measured the practice sites’ experience with various payment arrangements in the past, as this may indicate past opportunities to try different care management strategies and their adaptability to new operational processes (a count across the following: bundled or episode-based payments, primary care and support programs, pay-for-performance programs, capitated contracts with commercial health plans, Medicare upside-only risk-bearing contracts, and commercial ACO contracts) and predominant clinical population groups (i.e., adult, pediatric, or both), as this may indicate involvement of different types of clinicians, who have unique practice tendencies.…”
Section: Methodsmentioning
confidence: 99%
“…Explanations of why ACO programs have generally demonstrated mixed relationships with cost savings (Muhlestein et al, 2016; NAACOS, 2020) tend to focus on structural factors. For instance, better performance may be associated with an ACO being led by a physician organization (Peckham et al, 2019), having a larger number of attributed beneficiaries (Zhu et al, 2019), and having a larger proportion of primary care providers (Albright et al, 2016). However, many ACO-level structures are often difficult to modify in practice, and recent qualitative research has pointed to the often underappreciated importance of resources within ACOs that pertain to their linkages to frontline service delivery, such as coordination and feedback mechanisms (D’Aunno et al, 2018).…”
mentioning
confidence: 99%
“…As in similar studies, the analysis is based on a differencein-differences approach. Changes in mean spending in the project are compared with risk-adjusted mean changes in a control group, where the latter represent the expected outcome if the project had not been implemented (see, e.g., [6][7][8][9][10][11][12][13][14]). Using this approach, savings were estimated with large standard errors and were found to be very sensitive to high-cost patients.…”
Section: Estimating Savings Of 12 Pilot Projects On Integrated Carementioning
confidence: 99%